Cold plasma treatment is safe for diabetic foot ulcers and decreases Staphylococcus aureus bacterial load. (2nd April 2023) - Lagrand, Rimke S; Sabelis, Louise WE; de Groot, Vincent; Peters, Edgar JG
Abstract : Aim: Cold atmospheric plasma (CAP) has antimicrobial properties. We studied the safety of a novel CAP device (PLASOMA prototype; Plasmacure, The Netherlands) that is simple to use and could be applied at a patient's home for the treatment of diabetic foot ulcers (DFUs). Secondary objectives were to investigate the effect of CAP on bacterial load and on ulcer size. Method: We included subjects with non-infected, superficial DFUs and treated them with CAP on a daily basis for 10 days. The primary endpoint was the occurrence of serious adverse device effects (SADE). We defined safety as: ≤10% of patients experiencing a SADE other than infection (non-infectious SADE), and ≤60% of patients developing infection of the foot (infectious serious adverse event (SAE)). Results: We enrolled 20 patients. No SADE occurred, but three infectious SAEs occurred at the site of application within one month of treatment; three SAEs unrelated to treatment occurred, and 55% of subjects reported transient mild adverse device effects. Staphylococcus aureus bacterial load decreased directly after CAP application (p=0.01). The mean decrease of ulcer surface area was 43% (95% confidence interval: 20.2%–65.9%). Conclusion: CAP treatment in DFUs was safe and well tolerated. Ulcer size and Staphylococcus aureus colonisation decreased during treatment.